Persepsi Pengunjung Terhadap Taman Wisata Alam Madapangga, Kabupaten Bima : Visitors' Perception of Madapangga Nature Tourism Park, Bima Regency - Ijah, Uswatun; Anwar, Hairil; Webliana, Kornelia (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
Madapangga Nature Tourism Park (Taman Wisata Alam/TWA) is a conservation area with significant natural tourism potential, including diverse flora, fauna, springs, rivers, and scenic landscapes developed under ecotourism. However, its high tourism potential is not reflected in the number of visitors, indicating that the park's beauty and uniqueness have yet to attract substantial tourist interest. This study aimed to (1) assess visitors' perceptions in terms of four dimensions: Attraction, Accessibility, Amenities, and Ancillary Services, and (2) identify factors influencing visitors' perceptions regarding the management and appeal of the park.A qualitative descriptive approach was applied. Purposive sampling was used to select the site and respondents, and accidental sampling was used to collect data from 100 participants. Data analysis was conducted using a Likert scale.The findings revealed that 100% of respondents rated the attraction dimension as excellent. Regarding Accessibility, 80% considered access to the park good, while 20% rated it as less satisfactory. In the Amenities dimension, 99% of respondents rated the facilities as poor, and 1% as very poor. For Ancillary Services, 58% rated them as good, while 42% found them less satisfactory.Factors influencing visitor perceptions were classified into internal factors (age and education) and external factors (information and experience). Regression analysis showed that experience significantly influenced visitors' perceptions, while age, education, and information had no significant impact.This study highlights the importance of improving amenities and services to enhance visitor satisfaction and increase the attractiveness of TWA Madapangga as a tourist destination.